XBP1 May Determine the Size of the Ameloblast Endoplasmic Reticulum - Tsuchiya, M. (2008)
Ameloblasts progress through defined stages of development as enamel forms on teeth. Pre-secretory ameloblasts give rise to tall columnar secretory ameloblasts that direct the enamel to achieve its full thickness. During the maturation stage, the ameloblasts shorten and direct the enamel to achieve its final hardened form. Here we ask how the volume of selected ameloblast organelles changes (percent volume per ameloblast) as ameloblasts progress through six defined developmental stages. We demonstrate that mitochondria volume peaks during late maturation, indicating that maturation-stage ameloblasts maintain a high level of metabolic activity. Also, the endoplasmic reticulum (ER) volume changes significantly as a function of developmental stage. This prompted us to ask if X-box-binding protein-1 (XBP1) plays a role in regulating ameloblast ER volume, as has been previously demonstrated for secretory acinar cells and for plasma cell differentiation. We demonstrate that Xbp1 expression correlates positively with percent volume of ameloblast ER.